COMPARISON OF LOCAL AND IMPORTED OSTEOSYNTHETIC MANDIBULAR BONE PLATES IN TERMS OF MICRO HARDNESS IN MODIFIED SIMULATED BODY FLUID AT PERIODIC INTERVALS: Local and Imported Osteosynthetic Mandibular Bone - Anwar, Rabia; Kaleem, Muhammad; Baig, Amir Mushtaq; Saleem, Abida; Aslam, Ayesha; Jamal, Muhsin; Anwar, Farhana (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine the micro hardness of novel Pakistani manufactured osteosynthetic titanium bone mini plates (MPP) and imported osteosynthetic titanium bone mini plates (MPG) in body like conditions. Study Design: Descriptive study. Place and Duration of Study: This study was carried out at School of Chemical and Material Engineering, NUST from March to May 2013. Material and Methods: Microvicker hardness tester was used for assessment of micro hardness of two types of plates. The hardness was checked before conditioning and after conditioning at (six different places) on interval of 1, 7,14,21,28 and 40 days in modified simulated body fluid with ph 7.4 and temperature 370C. Results: Result showed that hardness of MPG was higher than MPP and after conditioning in simulated body fluid at all time periods, hardness of both types of plates was increased. Conclusion: It can be concluded from this study that micro hardness of imported plates is more than local plates so recommendations should be sent to manufacturers of local industry of Pakistan to improve the hardness of local plates so that they can meet international standards.